Analysis of the Effect of Brick Waste on Concrete Compressive Strength - Bayu Pramujya S; Fajar Mirdiana; Regan Muhammad I; Tira Roesdiana (Journal of World Science, 2025)
The construction industry generates significant red brick waste, often left unused and posing environmental challenges. Utilizing this waste as a substitute for fine aggregate in concrete can reduce reliance on natural materials and enhance concrete performance. Both red bricks and sand share a common silica (SiO?) content, making bricks a viable alternative material. This study evaluates the compressive strength of concrete incorporating red brick waste and identifies the optimal substitution percentage for maximum strength. Concrete samples (15x15x15 cm³) of K250 quality were tested with red brick waste replacing 0%, 6%, 8%, 10%, 12%, and 14% fine aggregate by weight. Compressive strength tests were conducted after curing periods of 7, 14, 21, and 28 days. Results indicate that adding brick waste significantly influences concrete strength. Concrete with 12% brick waste substitution achieved the highest compressive strength of 274.09 kg/cm², surpassing the strength of 6% substitution at 260.61 kg/cm². The findings demonstrate that red brick waste is a sustainable and effective alternative aggregate, contributing to environmental conservation and improved concrete performance. However, substitution proportions must be optimized to maintain desired structural properties.